The Physiological and Biochemical Mechanisms Bioprimed by Spermosphere Microorganisms on Ormosia henryi Seeds - Meng Ge; Xiaoli Wei; Yongming Fan; Yan Wu; Mei Fan; Xueqing Tian (Microorganisms)
The hard-seed coat of Ormosia henryi significantly impedes germination efficiency in massive propagation, while conventional physical dormancy-breaking methods often result in compromised seed vigor, asynchronous seedling emergence, and diminished stress tolerance. Seed biopriming, an innovative technique involving the inoculation of beneficial microorganisms onto seed surfaces or into germination substrates, enhances germination kinetics and emergence uniformity through microbial metabolic functions and synergistic interactions with seed exudates. Notably, spermosphere-derived functional bacteria isolated from native spermosphere soil demonstrate superior colonization capacity and sustained bioactivity. This investigation employed selective inoculation of these indigenous functional strains to systematically analyze dynamic changes in endogenous phytohormones, enzymatic activities, and storage substances during critical germination phases, thereby elucidating the physiological mechanisms underlying biopriming-enhanced germination. The experimental results demonstrated significant improvements in germination parameters through biopriming. Inoculation with the Bacillus sp. strain achieved a peak germination rate (76.19%), representing a 16.19% increase over the control (p < 0.05). The biopriming treatment effectively improved the seed vigor, broke the impermeability of the seed coat, accelerated the germination speed, and positively regulated physiological indicators, especially amylase activity and the ratio of gibberellic acid to abscisic acid. This study establishes a theoretical framework for microbial chemotaxis and rhizocompetence in seed priming applications while providing an eco-technological solution for overcoming germination constraints in O. henryi cultivation. The optimized biopriming protocol addresses both low germination rates and post-germination growth limitations, providing technical support for the seedling cultivation of O. henryi.